The Global Attic: An Address - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "The Global Attic: An Address," written by Walter B. Wriston for the Bankers' Association for Foreign Trade on 9 May 1972. The original speech is located in MS134.001.002.00016.